Storyworlds in Short Narratives : Approaches to Late Antique and Early Byzantine Tales - Andreou, Andria,; Constantinou, Stavroula, (Brill's Series on the Early Middle Ages ;, 2025)
This interdisciplinary and comparative volume offers a systematic approach to the early Greek tale. Bringing similarities and differences between ancient Greek and early Byzantine tales to the fore, this volume thus creates new knowledge in the fields of classics, medieval studies, and literary studies. Its chapters discuss the theory and poetics of tales, the art of storytelling, inherent features of the tale, and the arrangement, types, and characteristics of tales in collections. The chapter authors base their approaches on a rich variety of texts and writers that are here discussed for the first time in one volume. Contributors are: Andria Andreou, Stavroula Constantinou, Julia Doroszewska, Christian Høgel, Markéta Kulhánková, Ingela Nilsson, Nicolò Sassi, and Sophia Xenophontos.